Mothers and Traditional Birth Attendants: A Phenomenological Exploration of Childbirth Experiences - Alhikma, Alhikma; Owoeye, Isaiah Dada; Kiara, Francis Kirimi (Journal of Health Innovation and Environmental Education, 2025)
Purpose of the study: This study aims to explore the experiences of mothers giving birth assisted by traditional birth attendants in the working area of ​​the Parung District Health Center, Bogor Regency.Methodology: This study is a qualitative study with a descriptive phenomenological design through in-depth interviews. Participants include mothers who have given birth assisted by traditional birth attendants in the period from January to December 2014 obtained through purposive sampling. The data collected were in the form of interview recordings and field notes analyzed using the Colaizzi method.Main Findings: The results of this study can provide an overview to health workers that the existence of midwives cannot be denied from the lives of communities far from health facilities and the importance of understanding the psychological and sociocultural aspects of mothers who are about to give birth. Further research is needed on in-depth exploration of the psychological and sociocultural aspects of mothers giving birth.Novelty/Originality of this study: This study reveals the social and cultural dynamics that influence mothers' choices in using traditional birth attendant services, which have not been widely revealed in previous studies using a phenomenological approach.